Comparing the performance of people who stutter and people who do not stutter on the Test of Everyday Attention. Issue 6 (3rd July 2018) - Doneva, Silviya; Davis, Steve; Cavenagh, Penny
ABSTRACT: Introduction : Compelling findings into the relationship between stuttering and attentional ability have started to emerge, with some child and adult studies indicating poorer attentional ability among people who stutter (PWS). The purpose of the present research was to provide a more complete picture of the attentional abilities of PWS, as well as to gather insights into their individual attentional performance. Method : We compared the attentional ability of PWS to that of people who do not stutter (PWNS) by using the Test of Everyday Attention (TEA). TEA is a clinical assessment battery with a very good validity and reliability comprising 8 subtests that pose differential demands on sustained attention, selective attention, attentional switching, and divided attention. Fifty age- and gender-matched PWS and PWNS (aged 19–77 years) took part in the study. Importantly, we also examined stuttering severity in the PWS group. Results : PWS performed significantly worse on tasks tapping into visual selective and divided attentional resources. Furthermore despite failing to reach statistical significance, the results also revealed an interesting trend for stuttering to be associated with poorer performance on two subtests measuring attentional switching and one tapping into auditory selective attention. Moreover, as hypothesized, there was also a negative association between stuttering severity and performance on two TEA subtests measuring visual selective attention. Finally, the type of TEA test variant produced no significant effect on performance. Conclusions : We interpret these results as indicative of stuttering being associated with poorer performance on tasks measuring certain attentional abilities. These tie in well with theoretical models identifying speech production as particularly attention-demanding in stuttering or approaches placing attentional dysfunction at the heart of the condition. The present research also has practical implications for the use of attentional training to improve fluency.